The Effects of Pandemic to Face to Face Marketing Among the Senior High School Students in Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
It is important for every individual, especially students, to know the effects of the pandemic on face marketing to know how to handle their business to enhance and improve their strategies. In that case, every student must learn how to develop their ideas and strategies to handle this kind of problem. Therefore, the researchers chose this topic to give ideas and awareness on the effects of the pandemic on the market. So, the purpose is to help the students know enough to handle this kind of crisis. The school itself will benefit because the students will be knowledgeable about business. A descriptive design is used and suitable for this study. This study aims to know the effectiveness of social media in a small business among Senior High School students in Bestlink College of the Philippines. The tool used in this research is a survey questionnaire.  The researchers used Simple Random Sampling to select the fifty students to be respondents of this research. Based on the study's results, the pandemic's effects on face marketing among senior high school students addressed the above-cited factors and improved marketing in terms of (1) Loss of Business – some business owners chose to close their business because of the pandemic. (2) Exploring online marketing helps businesses experience face-to-face marketing and explore online marketing amid the pandemic. It helps the sellers to create new ideas to use. The researchers recommend that the students know the effective strategies for their business. To the sellers and consumers to give them some idea on how they can handle it to sell their product efficiently amid the pandemic. Parents must support their children so they will be more encouraged to learn. Lastly, Future Researchers must conduct more studies on the effects of the pandemic on marketing and effective business strategies.
Keywords: Face to Face Marketing